Non-specialized general education instructors' confidence and self-efficacy in teaching general education subjects - Jherwin P. Hermosa; Richard C. Ampo (Northern Negros State College of Science and Technology (NONESCOST), 2022)
The new General Education Curriculum offers a greater solution to the problems of higher education, particularly in the duplicity of subject areas that could be taken already at the senior high school level. Thus, this study was done to determine the level of confidence and self-efficacy of the non-specialists' instructors in teaching General education subjects. The descriptive-correlational design with self-constructed questionnaires was employed using 60 respondents. Frequency count, percentage, and mean were used in the descriptive statistical test while Pearson correlation analysis was used to determine the relationship of the main variables. Results revealed that the level of confidence in terms of commitment and personal experience is very high. While the level of self-efficacy in terms of performance outcomes and verbal persuasion is very high. Moreover, it was found that there was a significant relationship between the respondents' confidence and self-efficacy. It is recommended that instructors may look to incorporate biographical analysis in teaching GEC subjects. Administrators may pioneer a calibration program for non-GE instructors to increase opportunities to improve mastery of materials. Future researchers may use a different variable, larger respondents, and mixed methods to validate or contradict the result of this study.